Linkages between workplace stressors and quality of care from health professionals' perspective - Macedonian experience - Jovanka Karadzinska-Bislimovska; Vera Basarovska; Dragan Mijakoski; Jordan Minov; Sasho Stoleski; Angeleska, Nada; Atanasovska, Aneta (Wiley, 2014)
During last two decades, within the process of transition, the socio-economic reforms in Republic of Macedonia reflected on the national health care system. The objective of this article was to identify workplace stressors and factors that influence quality of care, from the perspective of health professionals (HPs), and to understand how they were linked in the context of such social circumstances.